The contribution of the EPZ to the economic growth of Mauritius - Ramasamy, Jaysen Kovalen (My University, 2015)
The story of the Export Processing Zone (EPZ) in Mauritius from its creation in 1970 through to its take-off and success is seen as an exception on the African continent. In the 1970s, very few African nations were able to create an EPZ and those that did were not as successful as Mauritius. We start off by investigating whether Mauritius had the unique characteristics of being blessed with the necessary political economy factors that provided an environment conducive to the creation of the EPZ. Factors such as inclusive institutions prior to and after independence, ideas, luck, leadership, dual-track economic strategy, ethnic diversity/diaspora and protection of vested interests contributed to the unique framework within which the Mauritius EPZ was created. Using an integrated approach where all factors have their own weight, we see that the protection of vested interests played an important role in determining the strategy of Mauritius to move towards the EPZ. The take-off and sustainability of the Mauritius EPZ throughout the 1980s are explained through the New Trade Theories, in particular the Krugman and Venables model, which explains success in terms of transport costs and low wages. We developed the hypothesis that it was a combination of both trade preferences and low wages that contributed to the exceptional EPZ growth in Mauritius. Using cross-country data to examine the association between the EPZ and economic performance, it seems that although those countries adopting an EPZ tend to be globally more successful, a more in-depth analysis shows that this hypothesis cannot be proven statistically and adopting an EPZ does not necessarily lead to the general effect of making a country successful. This should, however, not stop us from thinking about possible scenarios regarding the effect of EPZ on success. The first scenario, which was confirmed by the probit results, is that those countries that were successful and had an EPZ would have experienced some success anyway with or without an EPZ. The second is the possibility that EPZs were adopted by countries that were already set up for success, but EPZs nevertheless contributed in some way to the scale of success. The question remains as to whether Mauritius would have been as successful as it has been if it had not adopted the EPZ. Finally in the wake of liberalisation and the removal of trade preferences, we use difference-in-difference estimation to show that the Mauritius EPZ did not actually xv experience the failure that the prophets of doom had predicted; on the contrary, Mauritius was able to cope effectively with the removal of preferences. Actually, the removal of preferences did have an impact but the negative effect on the performance indicators was less than expected.
Thesis (Ph.D.)--University of the Witwatersrand, Faculty of Commerce, Law & Management, School of Economic and Business Sciences, 201